2019
DOI: 10.1177/1049732319858325
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Health Care Provider Needs and Preferences in Understanding Pharmacogenomic and Genomic Testing: A Meta-Data Analysis

Abstract: Tests that feature genomic indicators can now be used to guide the pharmacological treatment of patients. To better identify the needs and preferences of patients and health care providers in facilitating their understanding of information related to such pharmacogenomic tests (PGx), a review of literature on knowledge translation and health literacy in the context of testing was conducted. Using a grounded theory-based approach, a comparative analysis of data from 36 studies meeting the criteria for the meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…In line with research with patients [32,36], a sizeable majority of our public respondents endorsed receiving genetic counseling before undergoing sequencing. Accommodating this patient preference would have significant resource implications for healthcare systems, particularly in light of the well-documented lack of specialized genetic counseling services [37].…”
Section: Discussion/conclusionsupporting
confidence: 70%
See 1 more Smart Citation
“…In line with research with patients [32,36], a sizeable majority of our public respondents endorsed receiving genetic counseling before undergoing sequencing. Accommodating this patient preference would have significant resource implications for healthcare systems, particularly in light of the well-documented lack of specialized genetic counseling services [37].…”
Section: Discussion/conclusionsupporting
confidence: 70%
“…This might suggest an increased ability to think critically about ethical and clinical utility aspects of genomic information and promote informed decisions, raising questions about equity and informed access to genomic medicine. However, recent reviews of research on public and provider understanding highlight significant comprehension difficulties with genomic concepts and terminology [15,36], and suggest efforts to increase genomic literacy more broadly are needed. Research that creates and tests interventions to support the use of information related to genomic testing could help ensure realistic expectations for sequencing and promote informed sequencing decisions.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…As a result, the probability that a healthcare provider will be presented with PGx testing results is expected to increase (Bousman et al, 2019). This situation can be problematic in that many healthcare providers do not feel comfortable or confident using these test results due, in part, to concerns about the validity of the recommendations (Veilleux et al, 2020) or lack of transparency in how the recommendations were derived (Bousman and Eyre, 2020). In these cases, Sequence2Script can serve as a second opinion.…”
Section: Healthcare Providersmentioning
confidence: 99%
“…Brief and accessible materials may also be valuable to healthcare providers. A recent meta-data analysis found that many healthcare providers have never ordered a pharmacogenomics test, feel they are not well informed about such testing, and lack confidence to use pharmacogenomic results in their practice (Veilleux et al, 2020).…”
Section: Discussionmentioning
confidence: 99%